2015
DOI: 10.1210/en.2014-1137
|View full text |Cite
|
Sign up to set email alerts
|

PKCα and PKCδ Activation Regulates Transcriptional Activity and Degradation of Progesterone Receptor in Human Astrocytoma Cells

Abstract: Progesterone regulates cancer cell proliferation and invasion through its receptors (PR-A and PR-B), whose phosphorylation modifies their transcriptional activity and induce their degradation. We identified by in silico analysis a putative residue (Ser400) in PR that might be phosphorylated by protein kinase C (PKC), a family of enzymes involved in the proliferation and infiltration of astrocytomas, the most frequent and aggressive brain tumors. A grade III human astrocytoma-derived cell line was used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
(76 reference statements)
0
16
1
Order By: Relevance
“…However, while Natale et al did not find ER and PR, they found that melanocytes responded to oestrogen via fixation to GPER (G-protein coupled oestrogen receptor) and to progesterone via fixation to PAQR7 (progestin and adipoQ receptor 7), two G protein-coupled receptors. [20] Since various factors such as TPA, PMA, CT, insulin, IGF-1 and EGF [40][41][42][43][44] modulate ER and PR, we hypothesize that melanocytes are able to express ER, GPER, PR and PAQR7 but that their expression in vitro depends on stimulation by exogenous factors.…”
Section: Expression Of Sex Steroid Hormone Receptors In Melanocytesmentioning
confidence: 99%
“…However, while Natale et al did not find ER and PR, they found that melanocytes responded to oestrogen via fixation to GPER (G-protein coupled oestrogen receptor) and to progesterone via fixation to PAQR7 (progestin and adipoQ receptor 7), two G protein-coupled receptors. [20] Since various factors such as TPA, PMA, CT, insulin, IGF-1 and EGF [40][41][42][43][44] modulate ER and PR, we hypothesize that melanocytes are able to express ER, GPER, PR and PAQR7 but that their expression in vitro depends on stimulation by exogenous factors.…”
Section: Expression Of Sex Steroid Hormone Receptors In Melanocytesmentioning
confidence: 99%
“…Hormone receptor activation can also induce diverse signaling pathways like those mediated by MAPKs, PI3K/Akt, and PKC ( 25 27 ), regulate second messenger cascades ( 28 ) or modulate the actions of neurotransmitter receptors ( 29 ). These mechanisms are regulated through PR and ER located in the cytoplasm, nucleus, or plasma membrane ( 30 32 ) or through other membrane receptors that have different biochemical and pharmacological properties ( 33 , 34 ).…”
Section: Sex Hormones and The Brainmentioning
confidence: 99%
“…PKCα activates MAPK and MMP, thus increasing infiltration ability [112] ; PKCδ has been linked to radiation-induced apoptosis as well as MMP activation [119,120] ; and PKCε induces proliferation and apoptosis evasion [121] . Moreover, our group has reported that PKCα and PKCδ, through progesterone receptor phosphorylation, induce proliferation and migration [114] . However, further investigation is necessary to completely understand the role of different PKC isoforms in GBM growth as the effects of these kinases tend to be cell-specific and vary according to very particular cell conditions, hence complicating the use of PKC inhibitors in therapy.…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 94%
“…Once triggered, these proteins can activate and interact with other cascades such as MAPK and PI3K, and regulate processes such as proliferation, differentiation, apoptosis, and angiogenesis [110,111] . These events make PKC an important target in cancer, particularly in glioma where its importance has been thoroughly discussed [112][113][114] as PKC shows increased expression and activity in this kind of tumors [115] . There are reports indicating that PKC is important for progesterone-receptor-mediated proliferation in glioma cells, adding to the possible mechanisms of PKC function [114] .…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%
See 1 more Smart Citation